Knowledge Management in Vietnameses Mall and Medium Enterprises : Review of Literature - Hanh-Thao Le (Bright Institute, 2021)
This paper aims to review and analyze Knowledge Management (KM) in small and medium enterprises (SMEs) in the specific context of the Vietnamese economy using a literature review methodology. The important role of KM has been greatly emphasized in terms of achieving and maintaining a company's competitive advantage. However, most of the previous studies were conceptually based and examined empirically in developed, developed and industrialized countries and from a broad perspective. Meanwhile, little effort has been made to address the relative importance of KM in organizational infrastructure capabilities in the context of developing and less developed Asian countries such as Vietnam. The results show some of the current situation in Vietnam and related recommendations.